Blaze finds the trail - Anderson, C. W. (Clarence William), 1891-1971 (New York, NY : Aladdin Paperbacks, 2000)
Billy and his pony Blaze get lost in the woods with a storm approaching.
Ages 5-8.
Keywords: Ponies -- Juvenile fiction; Lost children -- Juvenile fiction